2020
DOI: 10.1016/j.otc.2020.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Robotic Surgery for Residual and Recurrent Oropharyngeal Cancers

Abstract: Transoral robotic surgery (TORS) for residual, recurrent tumors and new primaries in radiation-exposed fields is becoming increasingly adopted as more centers gain access to robotic systems and as favorable outcome data emerge. Achieving clear resection margins can be technically challenging in these cases and a TORS program should be considered only by experienced and appropriately trained surgeons. Transoral reconstruction additionally may be required Q9 and presents its own technical complexities. Successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…Additionally, the extent of resection and ability to achieve negative margins significantly impact diseasespecific and overall survival outcomes [23,24] . Defining HPV status is also a consideration, with some studies showing HPV-positive patients having improved overall survival after salvage surgery [3,25] . When considering salvage surgery as an option, the potential need for additional adjuvant therapy should also be considered, as additional radiation may further impair swallowing function and increase the risk of osteoradionecrosis [7] .…”
Section: Table 1 Outcomes After Salvage Tors For Oropharyngeal Malign...mentioning
confidence: 99%
“…Additionally, the extent of resection and ability to achieve negative margins significantly impact diseasespecific and overall survival outcomes [23,24] . Defining HPV status is also a consideration, with some studies showing HPV-positive patients having improved overall survival after salvage surgery [3,25] . When considering salvage surgery as an option, the potential need for additional adjuvant therapy should also be considered, as additional radiation may further impair swallowing function and increase the risk of osteoradionecrosis [7] .…”
Section: Table 1 Outcomes After Salvage Tors For Oropharyngeal Malign...mentioning
confidence: 99%
“…This supports comprehensive assessment before treatment, monitoring during radiotherapy, and follow-up as required in the longer-term post radiation and surgical management, and can be particularly useful in the setting of late effects and recurrent disease. 23 People undergoing surgery benefit from engaging with SLTs beforehand to learn swallow strategies that may become useful in their rehabilitation. This may reduce aspiration risk, maximise swallow outcome and reduce the length of post-treatment tube feeding.…”
Section: Establishing a Baselinementioning
confidence: 99%
“…Oropharyngeal carcinoma (OPC) occurring in a previously radiated field (ReRuNeR) comprises residual tumors that remained after radiation, recurrence of the tumor at the same site after a disease-free interval, and a new primary arising in a previously irradiated field [1]. Although ReRuNeR cancers after radiotherapy have specific molecular characteristics, they share common patterns of microscopic spread that make them more difficult to eradicate than primary tumors [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The surgical procedures significantly disrupt the normal anatomy and suffer from a high risk of postoperative complications, functional disability, and a major impact on the patients' quality of life (QoL) [6,8,11e14]. Due to its maneuverability in narrow spaces such as the upper aerodigestive tract, transoral robotic surgery (TORS) is now the preferred surgical option for treatment of T1-2 primary OPC with preservation of QoL [1,3,13,15]. For OPC after radiotherapy, a number of studies have demonstrated the feasibility and viability of TORS for small tumors [1,14e20].…”
Section: Introductionmentioning
confidence: 99%